A retrospective registry analysis of the transport‐related health burden of wheeled recreational devices in Queensland, Australia. (14th October 2021) - Rod, J.E.; Oviedo‐Trespalacios, Oscar; King, Mark
Abstract: Objective : Evaluate injury patterns from wheeled recreational devices (WRD) in the public space and explore risk factors for hospital admission. Method : A cross‐sectional analysis of WRD injury prevalence and risk factors for hospital admissions was conducted using data from the Queensland Injury Surveillance Unit (QISU) database for 2007 to 2017. Descriptive statistics and a log‐binomial regression model were used to calculate adjusted relative risk for hospital admission. Results : Most WRD injury in the public space was related to stand‐alone WRD injury events such as falls, with few reported WRD users being hit by vehicles from 2007 to 2017. Stand‐alone WRD injury events had a higher independent risk of hospital admissions when injured in the head/neck/face (RR 2.08, 95%CI 1.6 to 2.8, p<0.001), and when the injury was a fracture (RR 2.57, 95%CI 2.1 to 3.3, p<0.001) or a brain injury (RR 3.19, 95%CI 2.5 to 4.1, p<0.001). Conclusion : Head, brain and facial injuries and fractures are leading preventable factors for hospital admissions due to WRD injury. These types of injuries generate a preventable burden to the health system. Implications for public health : The results support the need to consider legislation regarding mandatory helmet use for non‐motorised WRD when used on public roads and footpaths, while further research is conducted. This strategy could reduce the long‐term health outcomes associated with head, face and brain injury in young commuters.